Phycobilins as Potent Food Bioactive Broad-Spectrum Inhibitors Against Proteases of SARS-CoV-2 and Other Coronaviruses: A Preliminary Study - Pendyala, Brahmaiah; Patras, Ankit; Dash, Chandravanu (Frontiers in Microbiology, 2021)
In the twenty-first century, we have witnessed three coronavirus outbreaks; SARS in 2003, MERS in 2012, and ongoing pandemic COVID-19. The search for efficient vaccines and development and repurposing evaluation of therapeutic drugs are the major approaches in the COVID-19 pandemic research area. Although, there are concerns about the evolution of mutant strains (For e.g.; VUI – 202012/01 – a mutant coronavirus in UK), which can potentially reduce the impact of the current vaccine and therapeutic drug development trials. One promising approach to counter the mutant strains is the “development of effective broad-spectrum antiviral drugs” against coronaviruses. In this study, we scientifically investigated potent food bioactive broad-spectrum antiviral compounds by targeting Mpro and PLpro proteases of CoVs using in silico and in vitro approaches. The results revealed that phycocyanobilin (PCB) showed potential inhibitor activity against both proteases. PCB had the best binding affinity to Mpro and PLpro with IC50 values of 71 µm and 62 µm, respectively. In addition, in silico studies with Mpro and PLpro enzymes of other human and animal CoVs indicated broad-spectrum inhibitor activity of the PCB. Like PCB, other phycobilins such as phycourobilin (PUB), Phycoerythrobilin (PEB), and Phycoviolobilin (PVB) showed similar binding affinity to SARS-CoV-2 Mpro and PLpro.